2016
DOI: 10.5433/1679-0359.2016v37n4p2167
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of tambaqui semen using a dry shipper and a programmed freezing machine

Abstract: Tambaqui (Colossoma macropomum) is a native freshwater fish that is of great importance for Brazilian aquaculture. Because of this importance, several techniques have been developed to improve the reproduction of this species in captivity. One of these techniques is the cryopreservation of sperm. In an effort to increase the efficiency of cryopreservation protocols, researchers have tried to determine suitable diluting solutions and freezing methods, which will provide a better post-thaw sperm quality. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
(19 reference statements)
3
10
2
5
Order By: Relevance
“…The use of activating solutions containing Na + ion to trigger fish sperm motility has been reported for many species. The NaCl solution has been used to trigger sperm motility of fish from different orders, such as characiforms B. insignis (present study; Viveiros et al, ), P. lineatus (Viveiros, Orfão, Maria, & Allaman, ) and Colossoma macropomum (Oliveira et al, ), cypriniforms Barbus barbus (Alavi, Rodina, Policar, & Linhart, ), Puntius conchonius (Hu, Zhang, Zhou, & Zhang, ), Vimba vimba (Alavi, Kozak, Hatef, Hamackova, & Linhart, ), Clinostomus elongatus (Butts, Alavi, Mokdad, & Pitcher, ) and Cyprinus carpio (Khara et al, ), and acipenseriforms Acipenser ruthenus (Alavi, Gela, Rodina, & Linhart, ), just to name a few. The NaHCO 3 solution has been used to trigger sperm motility of characiforms species, such as B. insignis (Viveiros et al, ), Leporinus obtusidens (Taitson, Chami, & Godinho, ) and Salminus brasiliensis (Weingartner, Zanandrea, & Zaniboni, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The use of activating solutions containing Na + ion to trigger fish sperm motility has been reported for many species. The NaCl solution has been used to trigger sperm motility of fish from different orders, such as characiforms B. insignis (present study; Viveiros et al, ), P. lineatus (Viveiros, Orfão, Maria, & Allaman, ) and Colossoma macropomum (Oliveira et al, ), cypriniforms Barbus barbus (Alavi, Rodina, Policar, & Linhart, ), Puntius conchonius (Hu, Zhang, Zhou, & Zhang, ), Vimba vimba (Alavi, Kozak, Hatef, Hamackova, & Linhart, ), Clinostomus elongatus (Butts, Alavi, Mokdad, & Pitcher, ) and Cyprinus carpio (Khara et al, ), and acipenseriforms Acipenser ruthenus (Alavi, Gela, Rodina, & Linhart, ), just to name a few. The NaHCO 3 solution has been used to trigger sperm motility of characiforms species, such as B. insignis (Viveiros et al, ), Leporinus obtusidens (Taitson, Chami, & Godinho, ) and Salminus brasiliensis (Weingartner, Zanandrea, & Zaniboni, ).…”
Section: Discussionmentioning
confidence: 92%
“…Colossoma macropomum (Oliveira et al, 2016), cypriniforms Barbus barbus (Alavi, Rodina, Policar, & Linhart, 2009), Puntius conchonius (Hu, Zhang, Zhou, & Zhang, 2009), Vimba vimba (Alavi, Kozak, Hatef, Hamackova, & Linhart, 2010), Clinostomus elongatus (Butts, Alavi, Mokdad, & Pitcher, 2013) and Cyprinus carpio (Khara et al, 2014), and acipenseriforms Acipenser ruthenus (Alavi, Gela, Rodina, & Linhart, 2011), just to name a few. The NaHCO 3 solution has been used to trigger sperm motility of characiforms species, such as B. insignis (Viveiros et al, 2011), Leporinus obtusidens (Taitson, Chami, & Godinho, 2008) and Salminus brasiliensis (Weingartner, Zanandrea, & Zaniboni, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of freezing rates within a dry shipper for cryopreservation of fish semen would generate a practical and field‐friendly technique to any species. Dry shipper is known to have more consistent freezing rates than other simple freezing methods, based on freezing samples in the middle of the interior space of dry shipper (Chew & Zulkafli, ; Horokhovatskyi et al, ; Koh et al, ; Oliveira et al, ). Relatively high freezing rates observed during the first 10 s of monitoring in this study were similar to the study reported by Taitson et al () who froze neotropical fish sperm ( Leporinus obtusidens ) in the dry shipper (model CP65, Taylor‐Wharton) with freezing rates of 25.7–30.8°C/s.…”
Section: Discussionmentioning
confidence: 99%
“…Dry shipper has recently been used as a freezing apparatus for the development of fish sperm cryopreservation program for aquaculture and conservation (Chew & Zulkafli, ; Gallego et al, ; Koh et al, ; Oliveira et al, ; Velasco‐Santamaría et al, ). To our knowledge, this study is the first report describing the successful cryopreservation of silver barb sperm by means of the dry shipper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation